Salience and health campaigns - Markus Dertwinkel-Kalt (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2015)
Motivated by current topics in health economics, we apply the theory of salience to consumer policy. If a government intends to stifle healthier diets without harming consumers by raising taxes, it could initiate information campaigns which focus consumers' attention either on the healthiness of one item or the unhealthiness of the other item. According to our approach, both campaigns work, but it is more efficient to proclaim the unhealthiness of one product in order to present it as a "bad." Our findings imply that comparative advertisement is particularly efficient for entrant firms into established markets.
Keywords: I18; D11; D03; 330; Salience; Health Policy; Information Campaign; Comparative Advertisement